Direct predictive current-error vector control for a direct matrix converter - Vijayagopal, Manjusha; Silva, César Armando; Empringham, Lee; De Lillo, Liliana (Institute of Electrical and Electronics Engineers, 2019)
This paper proposes a novel control strategy for matrix converters which is coined “Direct Predictive Current-error Vector Control”. The proposed control method retains the advantageous features of both a modulation scheme and of a predictive based controller. The result is a controller that is capable of good dynamic performance and steady state response with fixed switching frequency operation. Control of load and input currents of a direct matrix converter using the proposed method is demonstrated in this paper by simulation and experimental results.